The Kingdom Began in Puerto Rico : Neil Connolly's Priesthood in the South Bronx - Garcia, Angel (Book collections on Project MUSE., 2020)
How the South Bronx and Puerto Rican Migration defined Fr. Neil Connolly's priesthood as he learned to both serve and be part of his community.